Ocular biometric changes after Ahmed glaucoma valve implantation. Issue 1 (January 2021) - Miraftabi, Arezoo; Lotfi, Mahboubeh; Nilforushan, Naveed; Abdolalizadeh, Parya; Jafari, Samira
Purpose: To investigate the ocular biometric changes after uneventful Ahmed glaucoma valve implantation. Methods: Patients with refractory glaucoma who were candidate for Ahmed valve surgery were prospectively included in this study. Patients with a history of any kinds of corneal surgery were excluded. Refractive status, intraocular pressure, axial length, anterior chamber parameters including anterior and posterior mean keratometry, central corneal thicknesses, and anterior chamber depth, anterior chamber volume, and anterior chamber angle were evaluated at baseline and 1 and 3 months after surgery. Results: A total of 20 eyes from 20 patients were included. Mean intraocular pressure at baseline was 33.4 ± 12.3 mm Hg that significantly decreased to 14.6 ± 6.2 mm Hg at 1 month and 13.5 ± 4.3 mm Hg at 3 months after Ahmed glaucoma valve implantation ( p < 0.001). Mean number of medications was 3.6 ± 1.3 at baseline which significantly decreased to 1.0 ± 1.3 at 3 months after Ahmed glaucoma valve implantation ( p < 0.001). Axial length decreased significantly from 23.69 ± 1.95 to 23.47 ± 1.91 mm ( p < 0.001) at month 3. There were no significant changes in other parameters such as mean spherical equivalent, anterior chamber volume, anterior chamber angle, anterior chamber depth, and keratometry at the end of month 3 after surgery ( p > 0.05 in all). Conclusion: Ahmed glaucoma valve implantation had a significant effect on axial length at 3 months after surgery but its effect on keratometry and other anterior chamber parameters was not significant.